User preferences and consumer acceptability of boiled plantain in rural and urban localities in Cameroon - (:unkn) unknown (My University, 2024)
Source Agritrop Cirad (https://agritrop.cirad.fr/607433/) * Autres projets (id;sigle;titre): ;RTBfoods project;(FRA) Breeding RTB Products for End User Preferences//
Keywords: African Research